Efficient Synthesis of N-Alkyl Polyhydroxylated Pipecolamide Compounds from d-Glucurono-6,3-lactone - Kaddour, Alaa; Toumieux, Sylvestre; Wadouachi, Anne (Synlett, 2017)
N-Alkyl pipecolamides were efficiently synthesized from d-glucurono-6,3-lactone via a key 5-azido N-alkylamide intermediate that can be used as a scaffold for the synthesis of 4-amino and N-sulfonated pipecolamide derivatives.
Keywords: carbohydrates; d-glucurono-6,3-lactones; polyhydroxylated pipecolamides; iminosugars